Human G6PD variant structural studies: Elucidating the molecular basis of human G6PD deficiency - Alakbaree, Maysaa; Amran, Sayazwani; Mohd Shamsir, Mohd Shamsir; H. Ahmed, Haron; Hamza, Muaawia; Alonazi, Mona; Warsy, Arjumand; Ab Latif, Nurriza (Elsevier, 2022)
Glucose-6-phosphate dehydrogenase deficiency is by far the most prevalent human enzymopathy and is generated by a series of point mutations in the X-linked gene encoding G6PD. The severity of the deficiency relies on the various mutational sites in the gene, affecting the protein structure and function in at least two ways: by disrupting the entire protein fold or by altering the functional groups. Thus, the modified enzyme should be identified structurally and functionally to recognize the sequelae of each mutation. Understanding the molecular basis of G6PD deficiency is also essential to determine how mutations influence enzyme structure, stability, and activity. In characterizing 34 G6PD variants selected from Class I, II, and III, we reviewed and compared structural and molecular characterizations. These studies have shown that these mutations can influence the G6PD enzyme's local and global stability by changing the features of the mutant amino acids or by modifying their interactions (lost, increased, or decreased distances). Furthermore, the relationship between the changes in the enzyme structure and the severity of the disease was also reviewed. Overall, their results showed that Class I had the strongest influence on the protein's stability, activity, and function, which correlated with chronic nonspherocytic hemolytic anemia. Furthermore, there have been no drugs available to treat G6PD deficiency until now.